Agave angustifolia Century Plant, Variegated Caribbean Agave - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about the variegated Caribbean agave (Agave angustifolia), a striking plant known for its green leaves with bright white margins. It details the plant’s physical characteristics, including its height, spread, and leaf structure, as well as its growth requirements such as light, soil, and water needs. The document also covers the plant’s uses in landscaping, highlighting its suitability for rock gardens and as an accent plant. Additionally, it addresses the plant’s hardiness and invasive potential, noting that it is not recommended for cultivation due to its invasive nature. Original publication date September 1999.